Physical, morphological characterization and evaluation of pasting curves of musa spp. (2012)
Twenty varieties of Musa sp. from diverse genetic compositions were analyzed: AB, BB, AAA, AAB, ABB, AAAB and AAAA. The material was acquired from the Fedeplatano germplasm bank in Chinchiná, Colombia, located at 1360 masl. The varieties were physically and morphologically characterized, and their functional flour and starch properties were identified. The analysis of the principal components (PCA) showed that plantains are differentiated by their larger size (weight, length and diameter), when compared among varieties. MB Tani, ICAFHIA 110, Saba and Bluggoe plantain subgroups showed the largest peel percentages; the other clones did not differ from each other. Plantains for cooking from the Plantain subgroup (AAB), have more dry matter; Bocadillo Chileno and hybrid dessert (except FHIA 1) have more edible proportions than other varieties. The onset temperature for flour gelatinization in the RVA ranged from 66.58°C for Bocadillo Chileno, to 75.21 °C for Mbindi. The maximum viscosity was between 441.57 and 1837.17 cP for Red Tafetan and Dwarf Cavendish; cooking facility was between 2.76 and 7.55 minutes for the Bocadillo Chileno and Gros Michel Guayabo varieties. The onset temperature for starch gelatinization ranged between 65.58°C for Gros Michel Guayabo, and 74.41°C for Red Tafetan. The maximum viscosity was between 483.24 cP and 1958.44 cP for the varieties Yangambi Km3 and Indio. The Mbindi variety cooked more easily (1.91 minutes), while FHIA 1 needed more time (9.49 minutes).